Growth Performance of Silver Barb (Puntius gonionotus) in Mono and Polyculture Systems - Chaudhary, S.N.; Shrestha, M.K.; Jha, D.K.; Pandit, N.P. (Our Nature, 2009)
An experiment was conducted for 190 days from September 15, 2005 to March 25, 2006 in 12 outdoor concrete tanks of 24 m2 (4.9 m × 4.9 m) size and 1.25 m in water depth, at the Institute of Agriculture and Animal Science (IAAS), Rampur, Chitwan, Nepal to evaluate the growth performance and profitability of silver barb in mono and polyculture systems. The experiment was laid out in a completely randomized design (CRD) with four treatments having three replications each. There was one mono and three polyculture systems of silver barb with different fish species as treatments: (1) Silver barb at 1.5 fish/m2 (control); (2) Silver barb at 1.5 fish/m2 plus common carp at 0.2 fish/m2; (3) Silver barb at 1.5 fish/m2 plus male Nile tilapia at 0.3 fish/m2; and (4) Silver barb at 1.5 fish/m2 plus carps at 0.5 fish/m2 (silver carp 40%, bighead carp 20%, and common carp 40%). Silver barb were fed with 23% CP feed @ 4% body weight daily. At harvest, the mean weight, daily weight gain, gross fish yield (GFY) and net fish yield (NFY) of silver barb in monoculture treatment were significantly greater than in polyculture with common carp (p < 0.05), whereas there were no differences with polyculture with Nile tilapia (p > 0.05). However, survival of silver barb was not significantly different among treatments (p > 0.05). The combined GFY in polyculture with Nile tilapia treatment was significantly greater than in polyculture with common carp and in polyculture with other carps (p < 0.05). The NFY was highest in polyculture with Nile tilapia (4.4 ton/ha/yr), intermediate in polyculture with other carps (3.5 ton/ha/yr) and lowest in polyculture with common carp (2.9 ton/ha/yr) and monoculture (2.5 ton/ha/yr). Water quality parameters were not much difference in different treatments; however, water temperature was a crucial as it was less than 20°C for about 3 months (mid November to mid February). All the treatments produced positive net returns; however, the net returns were higher in polyculture with Nile tilapia than in other treatments. This study demonstrated that silver barb polyculture with male Nile tilapia is far better than other combinations. Keywords: Silver barb, Monoculture, Polyculture doi: 10.3126/on.v6i1.1653 Our Nature (2008)6:38-46